Premature stroke and cardiovascular risk in primary Sjögren's syndrome - Zippel, Clara L.; Beider, Sonja; Kramer, Emelie; Konen, Franz F.; Seeliger, Tabea; Skripuletz, Thomas; Hirsch, Stefanie; Jablonka, Alexandra; Witte, Torsten; Sonnenschein, Kristina; Ernst, Diana (Frontiers in Cardiovascular Medicine, 2022)
Introduction Primary Sjögren's syndrome (pSS) is associated with an increased prevalence of traditional risk factors and cardiovascular diseases (CVDs). The study aimed to identify specific risk factors for CVD in pSS patients. Methods PSS patients with and without CVD were compared. All patients fulfilled the EULAR/ACR classification criteria. Patients with CVD presented at least one of the following manifestations: myocardial infarction, transient ischemic attacks, ischemic or hemorrhagic stroke, peripheral artery disease, coronary artery disease, and carotid plaques. Data were collected by a standardized protocol and review of medical records. Results 61/312 (19.6%) pSS patients presented with CVD. Traditional risk factors such as hypertension, hypercholesterinemia and diabetes (p < 0.05), pSS manifestations, in particular vasculitis (p = 0.033) and Raynaud's phenomenon (p = 0.018) were associated with CVD. Among patients with ischemic events (28/312, 9%), particularly cerebrovascular disease (n = 12/28, 42.9%), correlations with increased EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) (p = 0.039) and EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) (p = 0.048) were observed. Age at first cerebrovascular event was 55.2 [48.9–69.6] years. Multivariate analysis confirmed hypertension [odds ratio (OR) 3.7, 95% confidence interval (CI) 1.87–7.18, p < 0.001], hypercholesterinemia (OR 3.1, 95% CI 1.63–5.72, p < 0.001), male gender (OR 0.4, 95% CI 0.17–0.78, p = 0.009), Raynaud's phenomenon (OR 2.5, 95% CI 1.28–4.82, p = 0.007), and CNS involvement (OR 2.7, 95% CI 1.00–7.15, p = 0.048) as independent CVD predictors. Conclusion Raynaud's phenomen as well as vasculitis and high ESSDAI have shown a significant association to CVD. PSS patients with cerebrovascular events were younger than expected. Knowledge about risk factors may help clinicians to identify pSS patients at risk for CVD. After diagnosis of pSS, patients should be screened for risk factors such as hypertension and receive appropriate therapy to prevent or at least reduce sequelae such as infarction. However, further investigations are necessary in order to achieve a reliable risk stratification for these patients.